Psychodrama and Moviemaking in a Death Education Course to Work Through a Case of Suicide Among High School Students in Italy - Testoni, Ines; Ronconi, Lucia; Palazzo, Lorenza; Galgani, Michele; Stizzi, Antonio; Kirk, Kate (Frontiers in Psychology, 2018)
This study describes the psychological effects of an experience of death education (DE) used to explore a case of suicide in an Italian high school. DE activities included philosophical and religious perspectives of the relationships between death and the meaning of life, a visit to a local hospice, and psychodrama activities, which culminated in the production of short movies. The intervention involved 268 high school students (138 in the experimental group). Pre-test and post-test measures assessed ontological representations of death, death anxiety, alexithymia, and meaning in life. Results confirmed that, in the experimental group, death anxiety was significantly reduced as much as the representation of death as annihilation and alexithymia, while a sense of spirituality and the meaning of life were more enhanced, compared to the No DE group. These improvements in the positive meaning of life and the reduction of anxiety confirmed that it is possible to manage trauma and grief at school with death education interventions that include religious discussion, psychodrama and movie making activities.